Ketepatan Koherensi Dalam Surat Kabar Waspada - Joko Hariadi (Program Studi Pendidikan Sejarah - Universitas Samudra, 2019)
This study analysed the development of paragraph, particularly coherence within the opinion column at newspaper of Waspada. It was done to investigate the coherence among sentences in a paragraph at column of that newspaper. The research employed the qualitative approach by means of descriptive research. The data resource was paragraphs in the column of Opinion at the newspaper of Waspada. The data were collected by direct observation toward the newspaper. Qualitative data analysis: data reduction, data display, and conclusion drawing, was done to analyse the data. It was found that errors in using sentence connectors were frequently made by the author of Opinion column of Waspada. It was suggested that the author make double-check before publishing the article to ensure that the readers can understand and comprehend the idea given in their articles.